Educação matemática e cidadania: um olhar através da resolução de problemas - Cavalcanti, Almir César Ferreira (2010)
In the process of retaking its journey concerning democracy construction, the Brazilian society faced a real boom of citizenship requirements originated from different groups which struggle for the right to live up to their own specificities. The mathematical education constitutes, thus, one of these requirements once the bond between education and citizenship is constant. Both of these are overlapped and they have been undergoing changes regarding time and space, in a cyclical movement, in the same way that society also changes. So, this requires an educated population for acting in the mentioned society. On the other hand, the population demands from this society an equality relation with respect for the rights and duties pertaining to the status that such education confers. In this way, this research aims to analyze the problems presented in the Mathematics didactic books in regard to formation and the citizenship exercise. The investigation had the purpose to answer the following question: In which way can Mathematics, as an integrated subject of one of the knowledge areas which make up the common national basis of the high school teaching curricula, collaborate for the accomplishment of a citizen formation? For this reason, after taking into account the Brazilian education legal bases, this research focused on understanding Mathematics while human construction aiming to define such knowledge area having as starting point man s fulfillments during his or her humankind s process. Furthermore, by considering a citizen formation, the goal was also to understand the construction and evolution of the citizenship concept along time and in different spaces. The option for approaching this formation arose from the possibility of exploring the statements of the mathematical problems contained in the didactic books. So, a close view on the problem concepts and resolution is essential as well as the influences received by them, and the consequences of such influences in the school curriculum. With the intention to understand the study object, the qualitative research and the interpretative method were used as approaches in order to analyze the content of the statements of the mathematical questions presented in the study of functions contained in two Mathematics didactic books recommended by the National Program of the High School Teaching Book (PNLEM). Such books were adopted by the majority of the state public schools in the city of João Pessoa PB. It can be concluded that Mathematics presented in the didactic books, by means of problems, and once such subject is taught in the educational process in a contextualized way, valuing the language and the mathematical content, and being connected to other knowledge areas, having thus an interdisciplinary character, can contribute for the formation of critical and participative citizens. It is still discussed that such Mathematics teaching is, however, a fundamental element for the mathematical formation as well as the construction of the student s citizenship (as social, historical and cultural subject). In this sense, the didactic book, and the didactic/pedagogic way that the teacher works with the mathematical problems in this book are constitutive elements of this educational process of citizen formation.